Door-to-Door Online Learning Assistance to Enhance Children's Learning Interest During the Covid-19 Pandemic - Masrifatin, Yuni; Makhmudah, siti; Laili , Fitriana; Hanifah , Risalatul; Mufarikhah , Thoyyibah; ainiyah, Fitratul (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This community service program aims to enhance the learning interest of elementary school students in Kemaduh Village, Baron District, during the COVID-19 pandemic, through a door-to-door online learning assistance method. The primary objective of this initiative was to provide direct learning support to students, especially in remote areas where access to technology and internet services is limited. The community service involved teachers, parents, and local community members in a collaborative effort to deliver personalized guidance to students, helping them overcome the challenges posed by online learning. The results showed a significant improvement in student engagement, understanding of learning materials, and parental involvement in supporting their children's education. This approach highlights the importance of community-based strategies in addressing educational inequalities during a crisis. The findings suggest that such door-to-door assistance can effectively increase student motivation and academic performance, even in areas with limited resources